2015
DOI: 10.1158/0008-5472.can-15-1626
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline Antibiotics Impair Mitochondrial Function and Its Experimental Use Confounds Research

Abstract: Tetracyclines, a class of antibiotics that target bacterial translation, are commonly used in research for inducible gene expression using Tet-ON/Tet-OFF systems. However, such tetracycline-inducible systems carry a risk. Given that mitochondria have a “bacterial” ancestry, these antibiotics also target mitochondrial translation and impair mitochondrial function. Indeed, treatment with doxycycline—a tetracycline derivative—disturbs mitochondrial proteostasis and metabolic activity, and induces widespread gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 28 publications
2
82
1
Order By: Relevance
“…Auwerx and colleagues (Chatzispyrou et al 2015;Moullan et al 2015) demonstrated that doxycycline negatively impacts mitochrondrial function. Doxycycline can also impact the gut microbiota in humans; the direct impact of this on adipose biology is unclear but potentially significant (Angelakis et al 2014).…”
Section: Perspectives Limitations and Future Directionsmentioning
confidence: 99%
“…Auwerx and colleagues (Chatzispyrou et al 2015;Moullan et al 2015) demonstrated that doxycycline negatively impacts mitochrondrial function. Doxycycline can also impact the gut microbiota in humans; the direct impact of this on adipose biology is unclear but potentially significant (Angelakis et al 2014).…”
Section: Perspectives Limitations and Future Directionsmentioning
confidence: 99%
“…An inhibitive effect of tetracycline on protein translation, which is managed by mitochondrial DNA on mammalian cells, has been reported. This inhibition will trigger the imbalance of mitochondrial protein, which will lead to interference with growth, oxygen consumption and fertility [24,25].…”
Section: Advances In Health Sciences Research Volumementioning
confidence: 99%
“…The cause of MDF is largely unknown but may involve genetic defects, ROS misbalance, impaired autophagy (mitophagy), alterations of signaling pathways, which regulate mitochondrial functions, retrograde pathway and mitochondrial unfolded protein response, acquired mutations in mtDNA or nDNA‐encoded mitochondrial genes, and inability of cells to overcome the consequences . A recent highlight arises from the detection of MDF in eukaryotic cells upon treatment with antibiotics . It has been demonstrated that even at low concentrations some antibiotics may inhibit mitochondrial functions and lead to detrimental changes on both molecular and physiological levels .…”
Section: Introductionmentioning
confidence: 99%